Influence of height in neuropsychological functioning and acquisition of motor milestones in children - Tomás Caycho Rodríguez (CAEN, 2014)
It aims to present a brief review on the effects of height above the sea level in neuropsychological functioning and the acquisition of motor milestones in children. While in Peru, there is no objective data to support such information, the reasoning described here is based on recent findings on the functional importance of the biophysical contexts that suggests the presence of slight alterations sensoperceptive functioning in high altitude conditions.